The prevalence of primary ovarian insufficiency in Sweden; a national register study - Katarina Lagergren; Mats Hammar; Elizabeth Nedstrand; Marie Bladh; Gunilla Sydsjö (BMC, 2018)
Abstract Background The current estimates of the prevalence of primary ovarian insufficiency (POI) are very variable, but are in most studies believed to be around 1%. It is also very likely tat the prevalence of POI differs between countries and over time. We therefore aimed to assess the prevalence of primary ovarian insufficiency in Sweden. Methods All 1,036,918 women born between 1973 and 1993 in Sweden were included. The prevalence of POI was based on data from the Swedish Patient Register through the diagnosis code or through the Prescribed Drug Register. The number of women below 40 years of age diagnosed with the ICD-10 diagnoses E28.3 or E89.4, and women who had been dispensed drugs for treatment of climacteric symptoms were included. Results Out of the 1,036,918 women, 19,253 (1.9%) had POI. The prevalence of spontaneous POI was 1.7% and the prevalence of iatrogenic POI was 0.2%. Most women (98.8%) with POI were identified from the Prescribed Drug Register; only 4.1% were found in the Patient Register, whereas 2.9% were identified in both registers. Conclusions The total prevalence of POI was 1.9%, 95% CI: 1.7-2.1, indicating a higher prevalence than often previously reported.